Hubungan Antara Durasi Bermain Game Online dengan Dry Eye Disease Menggunakan Tes Schirmer Pada Mahasiswa Prodi Pendidikan Dokter Universitas Nusa Cendana - Mario F.; Bilton Fun (Health & Medical Sciences, 2025)
This study examines the relationship between the duration of playing online games and dry eye symptoms among students of the Medical Education Program at the University of Nusa Cendana. Dry eye was assessed using the Schirmer test performed by an ophthalmologist. The research used a cross sectional design with 42 respondents selected through purposive sampling. The results show that all respondents who played for less than two hours per day had normal Schirmer test results. Among those who played for two to three hours, three respondents showed positive test results. Three respondents in the four to six hour group also showed positive results. One respondent who played for more than six hours had a normal result. Statistical analysis using Cramer’s V produced a p value of 0.218. This indicates no significant relationship between online gaming duration and dry eye based on the Schirmer test. These findings suggest that other factors beyond gaming duration may play a greater role in the occurrence of dry eye symptoms among students.